Characterization of MIS structures and thin film transistors using RF-sputtered HfO2/HIZO layers. (August 2017) - Hernandez, I.; Pons-Flores, C.A.; Garduño, I.; Tinoco, J.; Mejia, I.; Estrada, M.
Abstract: MIS structures using HfO2 and HIZO layers, both deposited by room temperature RF magnetron sputtering are fabricated for TFTs application and characterized using capacitance-voltage. The relative dielectric constant obtained at 1 kHz was 11, the charge carrier concentration of the HIZO was in the range of (2–3) × 10 18 cm − 3 and the interface trap density at flat band was smaller than 2 × 10 12 cm − 2 . The critical electric field of the HfO2 layer was higher than 5 × 10 5 V/cm, with a current density in the operating voltage range below 4 × 10 − 8 A/cm 2 . The hysteresis and bias stress behavior of RF-sputtered HfO2 /HIZO MIS structures is presented. Fabricated HfO2 /HIZO TFTs worked in the operation voltage range below 8 V. Highlights: Characterization of RF sputtered HfO2 /HIZO MIS structure Analysis of HfO2 /HIZO interface obtained by RF sputtering Reduction of operating voltage in HfO2 /HIZO TFTs